Petung, prosesi, dan sesaji dalam ritual manten masyarakat Jawa - Endah, Kuswa (Kejawen, 2025)
Petung, procession, and sesaji in the Javanese wedding ceremonial are social activities and rituals that still exist in the Javanese society. This activities are tradition that containt of values, norms, and spirituality symbolic aspects. The Javanese wedding prossesion have many varieties, namely: nontoni, nglamar, peningsetan, asok tukon, pingitan, tarub, midodareni, ijab, panggih, and tilik besan. This tradition activities are the way looking for life peace.